2013
DOI: 10.1158/0008-5472.sabcs13-p5-05-07
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-05-07: Promestriene effects on estrogen-sensitive breast cancer cell proliferation in vitro

Abstract: Introduction: Promestriene (3-propyl ethyl, 17B-methyl estradiol) is a synthetic estrogen analogue with potential as a topical treatment for vaginal atrophy caused by estrogen deprivation. Topical Promestriene is minimally absorbed with chronic use and has been reported to significantly improve the symptoms of vaginal atrophy. However, to be considered for use for these symptoms in estrogen responsive post-menopausal breast cancer survivors on an aromatase inhibitor, Promestriene would need to show none of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To further improve the safety of promestriene, especially in estrogen-sensitive cancer patients, a very low dose is used from the beginning, starting with half or less of the usual dose, and then gradually increased until the minimum effective dose, which could further reduce its already minimal vaginal absorption[ 196 ]. However, in vitro studies[ 197 ] concluded that the potential estrogen-like properties of promestriene to stimulate the growth of estrogen receptor-responsive breast cancer cell lines, especially in estrogen-deprived conditions, suggest caution when prescribing for vaginal atrophy in postmenopausal BCSs on AIs. Its ability to activate growth and gene expression in ER-BC cells warrants further study.…”
Section: Current Treatment Options For Genitourinary Syndrome Of Meno...mentioning
confidence: 99%
“…To further improve the safety of promestriene, especially in estrogen-sensitive cancer patients, a very low dose is used from the beginning, starting with half or less of the usual dose, and then gradually increased until the minimum effective dose, which could further reduce its already minimal vaginal absorption[ 196 ]. However, in vitro studies[ 197 ] concluded that the potential estrogen-like properties of promestriene to stimulate the growth of estrogen receptor-responsive breast cancer cell lines, especially in estrogen-deprived conditions, suggest caution when prescribing for vaginal atrophy in postmenopausal BCSs on AIs. Its ability to activate growth and gene expression in ER-BC cells warrants further study.…”
Section: Current Treatment Options For Genitourinary Syndrome Of Meno...mentioning
confidence: 99%
“…However, preclinical data have indicated that promestriene exposure could induce the proliferation of breast cancer cells expressing hormone receptors, especially under conditions of estrogen deprivation. Hence, caution is advised when considering its use for managing GSM in patients undergoing treatment with an AI [ 48 ].…”
Section: Introductionmentioning
confidence: 99%